Impact of Combined High-Fat Diet and Streptozotocin Exposure on Male Reproductive Health: Protective Role of Quercetin - O, Ajayi S.; G, Akunna G.; Nanle, Tongle; Omolara, Mosungu Ovayosa (Darul Yasin Al Sys, 2025)
Male infertility is an increasing global concern with profound social and psychological implications, often linked to metabolic dysfunctions such as Type 2 diabetes mellitus (T2DM). Streptozotocin (STZ), widely used to induce T2DM in animal models, is known to cause testicular toxicity through oxidative stress, inflammation, and apoptosis, thereby impairing spermatogenesis and hormone production. Quercetin, a flavonoid with established antioxidant and anti-inflammatory properties, has shown promise in ameliorating diabetes-related complications, including reproductive dysfunction. This study investigates the combined effects of a high-fat diet (HFD) and STZ exposure on male reproductive health, while assessing the protective role of quercetin. Fifty-four male Wistar rats were randomly assigned to nine experimental groups and subjected to HFD, STZ, and quercetin at different doses. Testicular health was evaluated by measuring absolute and relative testicular weights. STZ was administered intraperitoneally (30 mg/kg), and quercetin was administered orally at 50, 75, and 100 mg/kg for 28 days. Results showed that STZ-treated rats had significantly reduced testicular weight (1.00 ± 0.40 g) compared to controls (1.24 ± 0.07 g), confirming testicular toxicity. Quercetin supplementation, especially at 75 mg/kg (1.52 ± 0.37 g) and 100 mg/kg (1.48 ± 0.66 g), significantly restored testicular weight, suggesting a dose-dependent protective effect. These findings demonstrate that HFD exacerbates STZ-induced testicular toxicity, while quercetin confers substantial protection, supporting its potential as a therapeutic agent for managing testicular dysfunction in diabetic conditions.